Case studies of rock reinforcement components and systems testing - Thompson, A.; Villaescusa, Ernesto (2013)
Rock reinforcement is widely used in tunnels and surface and underground mines. A large number of proprietary products are available in various configurations of components. While the mechanical properties of the primary element are available from product brochures, the associated component properties may vary widely and adversely influence the overall performance of the system. Field pull out tests are most commonly used to measure the system response in the toe anchor region. However, the response of the collar region is less commonly considered but maybe more important. Several case studies are described in which various components and systems of rock bolts and cable bolts have been subjected to static loading in the laboratory and in the field. The results generally demonstrate the importance of considering the properties of all the components and not simply those of the primary element. In some cases, the internal fixtures have strengths much less than the elements. Often it has also been found that the fixture at the collar has significantly less strength than the element and this will result in complete loss of function in restraining surface support hardware such as plates, mesh and reinforced shotcrete. Copyright 2013 ARMA, American Rock Mechanics Association.